2017
DOI: 10.1080/14739879.2017.1338536
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Irish general practitioners’ preferences for continuing professional development

Abstract: The increasing diversity of services offered in the Irish primary care setting, in both clinical and non-clinical areas, should be tailored based to include GP practice location and structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…Several topics areas identified for future CPD topics/activities (e.g., perceived learning needs) intersect previous research findings [9,15,16]. For example, a recent study examining Irish general practitioners found that respondents highly endorsed educational activities related to practice management, ethics, and stress management [15]. Relatedly, Phitayakorn et al reported that a high percentage of surgical educators requested further training in research techniques, such as finding grant funding, designing research studies, and performing data analyses [16].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Several topics areas identified for future CPD topics/activities (e.g., perceived learning needs) intersect previous research findings [9,15,16]. For example, a recent study examining Irish general practitioners found that respondents highly endorsed educational activities related to practice management, ethics, and stress management [15]. Relatedly, Phitayakorn et al reported that a high percentage of surgical educators requested further training in research techniques, such as finding grant funding, designing research studies, and performing data analyses [16].…”
Section: Discussionsupporting
confidence: 77%
“…Several topics areas identified for future CPD topics/activities (e.g., perceived learning needs) intersect previous research findings [9,15,16]. For example, a recent study examining Irish general practitioners found that respondents highly endorsed educational activities related to practice management, ethics, and stress management [15].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…31 This, along with the positive findings seen in this study for stress, morale, and professional isolation, may be why the majority of GPs in Ireland use CME-SGL in preference to other methods available. 42…”
Section: Strengths and Limitationsmentioning
confidence: 99%